2015
DOI: 10.1016/j.biortech.2014.12.110
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis, characterization and enzymatic transesterification of single cell oil of Mucor circinelloides – A sustainable pathway for biofuel production

Abstract: The filamentous fungus Mucor circinelloides URM 4182 was tested to determine its ability to produce single-cell oil suitable for obtaining biodiesel. Cell growth and lipid accumulation were investigated in a medium containing glucose as the main carbon source. A microwave-assisted ethanol extraction technique (microwave power ⩽200 W, 50-60 °C) was established and applied to lipid extraction from the fungal hyphae to obtain high lipid concentration (44%wt) of the dry biomass, which was considerably higher than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 34 publications
4
58
0
Order By: Relevance
“…The lipid content achieved by CA is among the highest [10,11,13,44,45,62,63]. 3), being these values within the range referenced by other authors [46]. The lipid yield, glucose consumption, and lipid content showed that in CA approach, the consumed glucose was actively channelled for lipid biosynthesis.…”
Section: Combination Of High Aeration and 1% Of N-dodecane In Lipid Asupporting
confidence: 67%
See 1 more Smart Citation
“…The lipid content achieved by CA is among the highest [10,11,13,44,45,62,63]. 3), being these values within the range referenced by other authors [46]. The lipid yield, glucose consumption, and lipid content showed that in CA approach, the consumed glucose was actively channelled for lipid biosynthesis.…”
Section: Combination Of High Aeration and 1% Of N-dodecane In Lipid Asupporting
confidence: 67%
“…R. obliquus[64], A. pullulans[65] and M. circinelloides URM 4182[46]. obliquus[64], A. pullulans[65] and M. circinelloides URM 4182[46].…”
mentioning
confidence: 99%
“…The lipid content of M . circinelloides is typically around 25% [65], although gravimetric lipid yields up to 44% also have been reported [66]. The FTIR spectrum of the M .…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the ability of Metschnikowia sp. to produce PUFAs at a concentration of > 10 % is an interesting feature that could be of use in lipid applications in food, and in pharmaceutical and cosmetic formulations (Carvalho et al 2015). On the other hand, the use of low-cost lipid production by Metschnikowia yeast in non-sterile conditions (Santamauro et al 2014), makes the cultivation of this oleaginous yeast in crude glycerol very attractive.…”
Section: Fatty Acid Compositionmentioning
confidence: 99%